Erdheim‐Chester disease: An in vivo human model of Mϕ activation at the crossroad between chronic inflammation and cancer. Issue 2 (14th February 2020) - Cavalli, Giulio; Dagna, Lorenzo; Biavasco, Riccardo; Villa, Antonello; Doglioni, Claudio; Ferrero, Elisabetta; Ferrarini, Marina
Abstract: Erdheim‐Chester disease (ECD) is a rare histiocytosis characterized by infiltration of multiple tissues by CD68 + foamy Mϕs (or 'histiocytes'). Clinical manifestations arise from mass‐forming lesions or from tissue and systemic inflammation. ECD histiocytes harbor oncogenic mutations along the MAPK‐kinase signaling pathway ( BRAF V600E in more than half of the patients), and secrete abundant pro‐inflammatory cytokines and chemokines. Based on these features, ECD is considered an inflammatory myeloid neoplasm, and is accordingly managed with targeted kinase inhibitors or immunosuppressive and cytokine‐blocking agents. Evidence is emerging that maladaptive metabolic changes, particularly up‐regulated glycolysis, represent an additional, mutation‐driven feature of ECD histiocytes, which sustains deregulated and protracted pro‐inflammatory activation and cytokine production. Besides translational relevance to the management of ECD patients and to the development of new therapeutic approaches, recognition of ECD as a natural human model of chronic, maladaptive Mϕ activation instructs the understanding of Mϕ dysfunction in other chronic inflammatory conditions. Abstract : Mutation‐driven metabolic reprogramming and activation outcomes in Mϕs in Erdheim‐Chester disease